"Trump and racial equality in America? No pretense at all!". (2nd November 2021) - McClain, Paula D.
ABSTRACT: This article explores the effects of the Trump administration's racist words, policies, and behaviours on the increased racial divisions in the United States and the erosion of faith in American institutions. Many Americans have come to recognize that racial injustice is an enduring feature of American society. Recent events, such as the murder of George Floyd, have led to calls for racial justice. What is the definition of racial justice and how is it related to the concepts of structural inequality, systemic racism, structural racism, and institutional racism? The questions arises: What does racial justice look like in the present atmosphere in the United States? Is racial justice possible in a society riven by racial inequality? What about the wounds and scars from four years of Trump and his administration? Using a practical and policy-oriented definition of racial justice shows that Trump and his administration were not merely unconcerned about racial justice issues, but that they actually appeared to set out to exacerbate and inflame racial issues in the United States. Moreover, the damage done to the progress of America's communities of colour, especially Black Americans, continues to manifest itself, despite Trump no longer being in office.